Implementasi Peraturan Wali Kota Pangkalpinang Nomor 45 Tahun 2017 Tentang Pedoman Pengelolaan Pelayanan Informasi Dan Dokumentasi Di Lingkungan Pemerintah Kota Pangkalpinang - Yanto, Febri; Sartika, Ika (YUME : Journal of Management, 2024)
This research aims to evaluate the implementation of Pangkalpinang Mayor Regulation No. 45/2017 related to the management of information and documentation services. The method used is an empirical juridical approach, which combines legal analysis with field observation. Primary data was collected through interviews with relevant officials in Pangkalpinang City, while secondary data was obtained from literature studies. The results show that there are various obstacles in the implementation of this regulation, including limited human resources, lack of information technology infrastructure, and lack of socialization to the community. Other challenges are budget limitations and low public participation in utilizing the right to public information. In conclusion, while this regulation is important to increase transparency and accountability, improvement efforts are needed in terms of human resource capacity building, technology, and public socialization. This research provides recommendations to strengthen the implementation of information disclosure in Pangkalpinang City.